2020
DOI: 10.1371/journal.pone.0231218
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for patient non-compliance with compression stockings as a treatment for varicose veins in the lower limbs: A qualitative study

Abstract: The study aims to explore the comprehensive reasons for patients' non-compliance with graded elastic compression stockings (GECS) as the treatment for lower limb varicose veins. Phenomenological analysis was applied in this qualitative study. The patients diagnosed with lower limb varicose veins and undergoing elective surgery who showed non-compliance with GECS as the treatment were invited to have semi-structured, in-depth, face-toface interviews. Colaizzi method was employed to analyze the data for emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Ayala et al, 24 in a study of 889 patients with CVD in a tropical country, who were prescribed compression therapy, reported that only 31.8% wore it as prescribed. Noncompliance to compression therapy is the result of a multitude of factors, 25 one of which is that patients may complain that it does not immediately result in improvement of their symptoms. Ayala et al, 24 reported that the main reasons for noncompliance were that it was uncomfortable (49.4%), too difficult to put on (34.5%), caused skin problems (21.5%) and was unattractive (19.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Ayala et al, 24 in a study of 889 patients with CVD in a tropical country, who were prescribed compression therapy, reported that only 31.8% wore it as prescribed. Noncompliance to compression therapy is the result of a multitude of factors, 25 one of which is that patients may complain that it does not immediately result in improvement of their symptoms. Ayala et al, 24 reported that the main reasons for noncompliance were that it was uncomfortable (49.4%), too difficult to put on (34.5%), caused skin problems (21.5%) and was unattractive (19.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Compression is a conservative treatment used to treat varicose veins [ 91 ]. In a study conducted by Gavrilov et al.…”
Section: Treatmentmentioning
confidence: 99%
“…10 11 One of the reasons for non-compliance include difficulties putting ECS on and/or removing the ECS. [12][13][14][15][16] Some patients need assistive devices to preserve self-reliance, and a smaller proportion of patients rely on home care to assist with the application and removal of the ECS. The proportion of patients needing home care for this indication is not well known.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%